Implementation of the Bomb Snakes and Ladders Game Based on the ECOLA Learning Model to Improve Reading Skills in Elementary Schools - Pramiswari, Elok Dara; Mukhlishina, Innany (Journal of Education Action Reseach, 2023)
In PISA in 2018, Indonesia was ranked 74th out of 80 countries. In the reading ability category, Indonesia obtained an average score of 371, which is below the OECD average score of 489. In fact, literacy is an initial ability that every individual must have to live life in the future. Schools are responsible for creating a reading culture for students. This is a challenge for teachers to help increase students' reading motivation. This classroom action research aims to improve the reading skills of grade 5 elementary school students by implementing the ECOLA learning model based on the bomb snakes and ladders game. This research is a type of classroom action research (PTK) using two cycles. The design used in the research is the Kemmis and Mc Spiral model. Taggart was developed by Stephen Kemmis and Robin Mc Taggart in 1988. In one cycle there are four components including planning, action, observation and reflection in a spiral that are interconnected with each other. The subjects of this research were 24 grade 5 elementary school students consisting of 15 boys and 9 girls. Based on research that has been conducted, the use of the ECOLA learning model based on the bomb snakes and ladders game media can improve students' ability in reading skills. This is proven by an increase in the percentage of completeness of student learning outcomes from cycle I and cycle II learning.